Acute Psychosis in a Child with Severe Dengue - Bhatnagar, Ruchika; Prasad, Premlochan (Journal of Nepal Paediatric Society, 2018)
Dengue fever is emerging as an important cause of acute febrile illness with neuropsychiatric symptoms in adult population especially in endemic areas. Numerous case reports and review articles have already been published in past emphasizing on neurological manifestations in dengue but sufficient data on psychiatric symptoms in pediatric age group is still lacking. Acute psychosis in recovery phase of severe dengue is an uncommon phenomenon, thus rarely reported.